153k views
2 votes
@ 4x +(2x - 1) = x +5+x-6​

User Txtechhelp
by
5.2k points

2 Answers

5 votes

Answer:

I believe the answer is 4 but im not sure because I skipped the @ but I didnt know what it meant

Explanation:

User Synesso
by
4.8k points
0 votes

4x +(2x - 1) = x +5+x-6

pretend that there is a 1 in front of the bracket

4x+1(2x-1)= x+5+x-6

Mutiply the bracket by 1

(1)(2x)= 2x

(1)(-1)= -1

4x+2x-1=x+x+5-6( combine like terms)

6x-1= 2x-1

move 2x to the other side

sign changes from +2x to -2x

6x-2x-1= 2x-2x-1

4x-1=-1

move -1 to the other side

4x-1+1= -1+1

4x= 0

divide by 4 for both sides to get x by itself

4x/4= 0/4

Cross out 4 and 4, divide by 4 and then becomes 1*1*x= x

x= 0/4

Answer: x= 0

User Joseantgv
by
4.6k points